Development of microsatellite markers for the American species Vachellia aroma (Fabaceae, Caesalpinodeae) - Pometti, Carolina Luciana (2024)
Background and aims: There are currently no microsatellite markers available for any American species of Vachellia, and particularly, for V. aroma. Then the aims of this study were to develop SSR markers specific for V. aroma, for the first time, and test its amplification in a close related species. M&M: For the development of the SSR in V. aroma, total genomic DNA was extracted and it was sequenced in a one-fourth run on a Roche 454 GS FLX+ platform. The study area included two Argentinean populations: San José and Robles, Santiago del Estero province. Results: We detected 422 sequences containing SSR loci. A set of 39 primer pairs presented amplified products in V. aroma and V. caven, but 12 revealed clear, replicable and polymorphic loci in V. aroma. Conclusions: The results of this work indicate that a new set of SSR markers was developed for V. aroma and their transferability to V. caven was assessed. The analysis of variability, showed that these 12 polymorphic markers are highly informative, and a powerful tool to investigate population genetics parameters in V. aroma and related species.